Psicologia social e processo grupal: A coerência entre fazer, pensar e sentir em Sílvia Lane - Martins, Sueli Terezinha Ferreira [UNESP] (My University, 2007)
The present article discusses historic and dialectical conceptions of group process by Sílvia Lane, that uses like base for her reflections the presuppositions of dialectical materialism, when the author considers the personal aspects, the group characteristics, the subjective existence and objective reality and the historical character of the group. This article intends to emphasize the production written by Sílvia Lane about group between 1980 and 1990 summaried in the text The group process. In this direction, it searchs to bring the contributions in her work through articles, collections and books that Sílvia Lane discusses some fundamental categories to the analysis of group process and their theoretical and methodological evolvement and practical-politics.
Social psychology and group process: Coherence between doing, thinking and feeling in Sílvia Lane
Keywords: Activity; Conscience; Group process; Psychology socio-historical